Fractures in Patients With COVID-19 Infection: Early Prognosis and Management. A Case Series of 20 Patients in a Single Institution in Lombardy, Northern Italy. Issue 10 (October 2020) - Jannelli, Eugenio; Castelli, Alberto; Ferranti Calderoni, Enrico; Annunziata, Salvatore; Maccario, Gaia; Ivone, Alessandro; Pasta, Gianluigi; Mosconi, Mario
Summary: Fifty-eight percent of the total infections in Italy of COVID-19 were found in northern Italy, in particular, Lombardy. From February 21, 2020, to March 23, 2020, 20 patients with a fracture and a diagnosis of COVID-19 were hospitalized. Demographic data, COVID-19 symptoms, laboratory and radiographic examinations, and treatment methods were recorded. At 1-month follow-up, patients were assessed with the SF-36 score. This case series includes 20 patients (16 women and 4 men), with an average age of 82.35 years (range 59–95). Eleven patients (55%) had a femur fracture. Fourteen patients (70%) had 3 or more comorbidities or previous pathologies. Three patients with severe comorbidities died during the hospitalization. Thirteen patients (65%) had fever, 18 patients (90%) asthenia, and 17 patients (85%) dyspnea. All patients (100%) were given antibiotic therapy, whereas 16 patients (80%) underwent hydroxychloroquine therapy and 8 (40%) were treated with corticosteroids. Eighteen patients (90%) underwent antithromboembolic prophylaxis. Eighteen patients (90%) had lymphopenia. All 20 patients (100%) required noninvasive mechanical ventilation. High D-dimer and polymerase chain reaction values were found in all patients (100%), whereas lactate dehydrogenase was increased in 18 patients (90%). Patients with fractures, especially in the lower limbs, frequently require hospitalization, making these patients more subjected to the risk of COVID-19 infection. COVID-19 infection therefore does not seem to influence the fracture pattern in the elderly population but can lead to health deterioration with increased mortality. The typical symptoms of COVID-19 disease have not changed when associated with a fracture or trauma. Laboratory data are in line with what is reported in recent studies, whereas a more invasive assisted ventilation is associated with a poor prognosis. Finally, analyzing the data obtained from the SF-36 score, significantly lower values emerged when compared with those reported in the literature. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.